Differential relations of executive functioning to borderline personality disorder presentations in adolescents. (1st February 2018) - Kalpakci, Allison; Ha, Carolyn; Sharp, Carla
Abstract: Borderline personality disorder (BPD) in adolescents is highly complex and heterogeneous. Within the disorder, research has suggested the existence of at least two subgroups: one with predominantly internalizing psychopathology features and one with predominantly externalizing psychopathology features. One process that may differentiate these groups is executive functioning (EF), given that poor EF is linked to externalizing psychopathology. Against this background, the current study used a multi‐informant approach to examine whether adolescent patients with predominantly externalizing BPD presentations experience greater deficits in EF than adolescent patients with predominantly internalizing presentations. The sample included inpatient adolescents ages 12–17 ( M  = 15.26; SD = 1.51). Analyses revealed that multiple EF domains distinguished the BPD subgroups. More specifically, adolescents with externalizing presentations exhibited greater difficulties in broad domains related to global executive functioning, metacognition and behavioural regulation and specific domains related to inhibitory control, working memory, planning/organizing, monitoring and organization of materials. While this study is the first to examine EF and adolescent BPD in the context of internalizing and externalizing psychopathology, alternative approaches to examining this question are discussed. Copyright © 2018 John Wiley & Sons, Ltd.